Non-pecuniary damages in the "missing babies" cases - law enforcement experiences - Arsenijević, Bojana (Glasnik Advokatske komore Vojvodine, 2025)
The Act on Establishing the Facts about the Status of Newborn Children who are Suspected of Having Disappeared from the Maternity Hospitals in the Republic of Serbia was adopted in 2020. Colloquially known as the Missing Babies Act, it regulates the right of parents and relatives to fair monetary compensation for non-pecuniary damage in case of violation of their right to respect the family life. The paper presents the first analysis of the results of the implementation of this Act in regard of awarding non-pecuniary damages. Empirical research was conducted in the High Court in Novi Sad, the High Court in Belgrade, the High Court in Kragujevac and the High Court in Niš. Using the statistical and the random sample methods, the research analyses court cases involving request for compensation of non-pecuniary damages resulting from the infringement of one’s right to respect for family life in the “missing babies” cases. The paper examines the earlier judicial practice in similar factual cases, with special reference to the judgment of the European Court of Human Rights in the case of Zorica Jovanović v. Serbia (appl.12794/08). Furthermore, using the normative and comparative law methods, the paper presents the analysis of non-pecuniary damages and its purpose. The paper aims to provide a theoretical and empirical analysis of the court judgments awarding of non-pecuniary damages in the “missing babies” cases for violation of the right to respect for family life. According to the research findings, parents’ decades-long struggle yielded a Pyrrhic victory in a form of monetary compensation for non-material damages but, in a vast majority of cases, there was no information regarding the actual fate of the missing children.